GIS in Education Planning: The Kenyan School Mapping Project - Mulaku, G.C.; Nyadimo, E. (Survey Review, 2011)
School mapping consists of the building of geospatial databases of educational, demographic and socioeconomic data for educational institutions in order to support educational planning and decision making. Such databases contain data such as the geographic location of schools, the numbers of existing schools of different levels in the public and private sectors, their capacities, physical condition and facilities, enrolment and the number of teachers and their attributes. Also often included are data on related natural features and infrastructure such as rivers, roads, economic and administrative centers, medical facilities, religious facilities, etc. This paper describes the Kenyan School Mapping Project, whose objective was to collect such data for all Kenyan learning institutions and to integrate them in a GIS database that could be queried to provide useful information for educational planners, other professional users and average citizens. Results show that at the time of the project, there were nearly 73000 learning institutions in Kenya, ranging from early childhood schools to universities; useful information products on important educational indicators such as schools distribution, enrolments, pupil-teacher ratios and gender parity indices have also been generated from GIS analysis of the data. These results have demonstrated the utility of the database for its stated purpose and therefore shown the project to be a useful model that can be emulated by other developing countries.
Publisher: Taylor & Francis _eprint: https://doi.org/10.1179/003962611X13117748892155 KerkoCite.ItemAlsoKnownAs: 10.1179/003962611X13117748892155 2405685:HH3GP4V2 4042040:NJ6E8C3M
Keywords: EMIS; GIS; KENYA; SCHOOL MAPPING

Literature Reviews of Educational Technology Research in Low- and Middle-Income Countries: An audit of the field - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
previousShortDOI: 10/ghgnfn previousShortDOI: 10/ghgnfn previousDOI: 10.5281/zenodo.4779020 previousDOI: 10.5281/zenodo.4768577 previousDOI: 10.5281/zenodo.3594489 previousShortDOI: 10/ghgnfn EdTechHub.Copy: 2129771:USWMWK73 previousShortDOI: 10/ghgnfn KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3523943 10.5281/zenodo.3594489 10.5281/zenodo.4768577 10.5281/zenodo.4779020 10.53832/edtechhub.0015 10/ghgnfn 2129771:K852X3EV 2129771:T7BUZI5N 2129771:USWMWK73 2339240:5KS58AH6 2339240:NZDE37HY 2405685:NM6CPLE9 2405685:SSWKT2MV 2405685:TDVP3W34
Keywords: LP: English; R:Literature review; systematic review; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:g; _zenodoETH:submitted; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode; educational technology; EdTech; low-income countries; literature review

Reviewing the research literature in educational technology for development: Balancing rigour and inclusivity - Jordan, Katy (EdTech Hub, 2019)
shortDOI: 10/ghgnf5 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3581041 10/ghgnf5 2405685:YXIGT4W9
Keywords: LP: English; R:Literature review; systematic review; _DOILIVE; _EdTechHub_Output; _zenodoETH

Moving teachers to Malawi’s remote communities: A data-driven approach to teacher deployment - Asim, Salman; Chimombo, Joseph; Chugunov, Dmitry; Gera, Ravinder (International Journal of Educational Development, 2019)
There are severe geographical disparities in pupil-teacher ratios (PTR) across Malawi, with most teachers concentrated near commercial centers and in rural schools with better amenities. Most of the variation in PTR is concentrated in small sub-district areas, suggesting a central role for micro-geographic factors in teacher distribution. Employing administrative data from several government sources, regression analysis reveals that school-level factors identified by teachers as desirable are closely associated with PTR, including access to roads, electricity, and water, and distance to the nearest trading center, suggesting a central role for teachers’ interests in PTR variation. Political economy network mapping reveals that teachers leverage informal networks and political patronage to resist placement in remote schools, while administrative officials are unable to stand up to these formal and informal pressures, in part because of a lack of reliable databases and objective criteria for the allocation of teachers. This study curates a systematic database of the physical placement of all teachers in Malawi and links it with data on school facilities and geo-spatial coordinates of commercial centers. The study develops a consistent and objective measure of school remoteness, which can be applied to develop policies to create rules for equitable deployments and targeting of incentives. Growing awareness of disparities in PTRs among district education officials is already showing promising improvements in targeting of new teachers. Simulation results of planned policy applications show significant potential impacts of fiscally-neutral approaches to targeted deployments of new cohorts, as well as retention of teachers through data-calibrated incentives.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2018.12.002 2339240:7QKQHXG2 2405685:GWKND7GG
Keywords: Data-driven model; Deployments; Malawi; Political economy; Schools; Teachers

Literature search protocol for the African Education Research Database - Mitchell; Rose (Zenodo, 2018)
This methodological note provides an overview of the ‘Mapping education research in sub-Saharan Africa’ project. It presents the protocols for the literature search, data extraction, and development of the African Education Research Database.
shortDOI: 10/ghgnfp KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1245521 10/ghgnfp 2339240:3WYP59B9 2405685:CK2VGGRV
Keywords: Reviewed; _not_EdTechHub; _zenodoOTHER; education research; sub-Saharan Africa

An Atlas of The Forty Colleges of Education in Ghana - Haßler, Björn; Akunor, J. T.; Nyamador, E. S. (2017)
EdTechHub.Source: 2129771:F7ZRYUZX shortDOI: 10/ghgk6m KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3911076 10/ghgk6m 2129771:F7ZRYUZX 2129771:U3IVX9WX 2405685:SKFNBK29
Keywords: _DOILIVE; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Synergies Between the Principles for Digital Development and Four Case Studies - Haßler, Björn; Broadbent, E.; Cunningham, A.; Chimombo, J.; Jamil, B. R.; Kauthria, R.; Lake, L.; Rose, P.; Sarfraz, S.; Szekely, M. (Research for Equitable Access and Learning (REAL) Centre, Faculty of Education, University of Cambridge, 2018)
This report was prepared by Bjöern Haßler for the Research for Equitable Access and Learning (REAL) Centre, University of Cambridge, UK, with support from the Global Education & Skills Forum (GESF) Alliance on Assessment and Impact for Learning. This Alliance was co-chaired by Pauline Rose (REAL Centre, University of Cambridge, United Kingdom) and Baela Raza Jamil (Idara-e-Taleem-o-Agahi, Pakistan) and included the following members: Emma Broadbent (The Varkey Foundation, United Kingdom), Andrew Cunningham (Aga Khan Foundation, Switzerland), Joseph Chimombo (Ministry of Education, Malawi), Rashmi Kauthria (Global Teacher Prize Finalist 2017, India), Lucy Lake (Camfed, United Kingdom), Shajia Sarfraz (Independent Researcher, Pakistan) and Miguel Szekely (Center for Education and Social Studies, Mexico).
shortDOI: 10/ghgngb KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1196830 10.5281/zenodo.1219919 10/ghgnf9 10/ghgngb 1867969:MS4YEFUV 2129771:3HPEHK45 2339240:6UEQFTXM 2339240:HYX3RTJZ 2339240:WNVALD7D 2405685:A8G2S2ZT 2405685:FUKJ5SE8 2405685:IGGQMIXI 2405685:PWCIYQJM
Keywords: _DOILIVE; ___working_potential_duplicate; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Sustaining and scaling pedagogic innovation in sub-Saharan Africa: Grounded insights for teacher professional development - Haßler, Björn; Hennessy, Sara; Hofmann, Riikka (Journal of Learning for Development, 2018)
Developing sustainable and scalable educational initiatives is a key challenge in low-income countries where donor-funded short-term projects are limited by both contextual factors and programme design. In this concept paper we examine some of the issues related to in-service teacher development in the context of sub-Saharan Africa, grounded predominantly in our experiences of over 5 years of iteratively developing, refining and evaluating an intensive school-based professional learning programme for primary school teachers. “OER4Schools” integrates interactive pedagogy, Open Educational Resources (OER) and use of mobile devices (where available). The focus of this paper is on identifying what the main factors are perceived to be in sustaining and scaling up such a programme, from the perspectives of participating teachers, workshop facilitators and the research team. Synthesising our previous research and drawing on recent work in the field, we identify the key characteristics of effective and sustainable professional learning in low-resourced contexts. Such characteristics include effective peer facilitation, school-based active learning, explicit programme structure, appropriate scheduling and resourcing, and mitigating resource constraints through use of OER. Our conclusions thereby offer insights concerning the importance and impact of wider influences on participation and engagement of stakeholders and lead to recommendations for programme design and implementation, that should be taken on board by future initiatives.
00000 EdTechHub.Source: 2129771:D2GQYC5S KerkoCite.ItemAlsoKnownAs: 10.56059/jl4d.v5i1.264 2129771:43ZT3XWL 2129771:52KKAHKR 2129771:AAT7FR3H 2129771:D2GQYC5S 2129771:LDWSNI7T 2129771:LHMXV7QF 2249382:CS9PALG8 2317526:6IH7CD39 2317526:PP4CHVEG 2339240:2BCABLG6 2339240:4N3G4XDJ 2339240:9BPXVI62 2339240:C7CKIPL7 2339240:D83N6FTA 2339240:HGHAYJ5G 2339240:HR2YGWX3 2339240:P65I7MGU 2339240:YSVITTWH 2405685:3GSCKVWC 2405685:7X2D9JDG 2405685:CUHYHFLV 2405685:M8UDHT7A 2405685:NKSYKNQN 2405685:NVEVT9HX 2405685:NZ3GKZCR 2405685:T2I86FZT 2405685:ZFJ79LQS 2486141:Z3PRLX4K 257089:AJJPQKDF 261451:JC3NQMN3 261495:BWD9L8FL 261495:TCP47GGI
Keywords: AWP2; Active Learning; Africa; Author:Haßler; C:sub-Saharan Africa; CitedIn:DFID_SRF; CitedIn:OER4S-TPE-Anon; CitedIn:OER4Schools-2012-HHH1-anon; CitedIn:PhD_Thesis; DIAL-RDO; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; IMPORT_FROM_DFID_RITE; InPrep; Inservice Teacher Education; Low Income Groups; Motivation; OER4Schools; Open Educational Resources; Peer Teaching; RPF-May-2016; Resource Allocation; Rural Schools; Scaffolding (Teaching Technique); Scheduling; Shared Resources and Services; Sustainable Development; Sustainable Development Goal 4; Teacher Professional Development; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; dode_eth-src-dode; dode_eth-trf2-dode; missingHU; peer-facilitation; school-based active learning; sub-Saharan Africa; ⛔ No DOI found

Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) - Haßler, Björn; Brugha, Meaghan; Muyoya, Chisenga; Mitchell, Joel; Hollow, David; Jackson, Alan (Jigsaw and Open Develoment & Education, 2018)
Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) Also available at https://digitalprinciples.org/resource/donor-organizations-the-principles-for-digital-development-a-landscape-assessment-and-gap-analysis/, https://digitalprinciples.org/wp-content/uploads/PDD2018_interactive.pdf
EdTechHub.Source: 2129771:I2CG3TP3 shortDOI: 10/ghgk6z KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1204703 10/ghgk6z 2129771:I2CG3TP3 2129771:SI7RBL6P 2405685:46SDL9HI
Keywords: _DOILIVE; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Tablet use in schools: a critical review of the evidence for learning outcomes - Haßler, Björn; Major, Louis; Hennessy, Sara (Journal of Computer Assisted Learning, 2016)
EdTechHub.Source: 2129771:9IYKEUKJ shortDOI: 10/f8f6mc KerkoCite.ItemAlsoKnownAs: 10.1111/jcal.12123 10/f8f6mc 2129771:6YGVDBXS 2129771:9IYKEUKJ 2129771:BFWTG2BG 2129771:HX6DBG7W 2317526:3V7LV2NP 2339240:C6LDZSDW 2339240:GNBA7ZJI 2339240:WPK23R37 2339240:YYGY6J8F 2405685:7552P2EL 2405685:9I6F956M 2405685:J6HBWCZL 2405685:SZ2DB7K2 503888:U6FRZHMB
Keywords: Android; Author:Haßler; dode_eth-src-dode; dode_eth-trf2-dode; iPad; learning outcomes; school; systematic reviews; tablets

Mother tongue as default language of instruction in lower primary science classes: Tension between policy prescription and practice in Nigeria - Okebukola, Peter Akinsola; Owolabi, Olatunde; Okebukola, Foluso Olutoyin (Journal of Research in Science Teaching, 2013)
The forecast for the first quarter of this century is that the issue of teaching science in the language to which the learner is most familiar will receive more attention in our quest to win more students for science. Over two-thirds of countries in Africa, Asia, and Europe have developed policies on the use of the mother tongue for teaching science in the lower levels of their education system. In spite of this policy thrust, the educational system of many of these countries has not responded fully to the demands of such a policy. Because studies which mapped the dynamics of communication in science classrooms taught using the mother tongue are scant, we remain in the dark as to how best to structure such classrooms. The study was conducted in 12 primary schools and it involved 36 teachers in urban and rural locations of Lagos State, Nigeria. Quantitative and qualitative data were collected from primary science classrooms where the mother tongue is expected to be used as a medium of instruction. Mismatch between policy and practice was found especially in urban science classrooms. Among other things, it was found that on the average, science lessons delivered in primary 1 in rural settings, were found to be 93.6% in the mother tongue (L1). In primary 2 this fell to 91.1% and in primary 3–84.6%. In contrast, in the urban schools, mother tongue content was found to be 61.8% in primary 1, 49.2% in primary 2 and 26.6% in primary 3. The geo-spatial communication between and among pupils in urban and rural science classes also showed interesting findings, that is, English served as a mediating language. The implications of the findings for future policy considerations and future research to inform policy are drawn. © 2012 Wiley Periodicals, Inc. J Res Sci Teach 50:62–81, 2013
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/tea.21070 KerkoCite.ItemAlsoKnownAs: 10.1002/tea.21070 2405685:FM277GAH 4042040:XENETYQZ
Keywords: class dynamics; mother tongue; science teaching